Intoxicación aguda por plaguicidas: Comparación de las características epidemiológicas entre la población rural y urbana - John Alexander Benavides; Jeadran N. Malagón-Rojas; Luisa Fernanda Lagos; Thereza Christina Bahia Coelho; Yenny Alejandra Vasquez Lozada; Mónica Alejandra Quintana Cortés; Alejandra del Pilar Díaz-Gómez; Mario A. Hernández (Universidad de Antioquia, 2023)
Objective: To analyze the behavior of pesticide poisoning in rural and urban populations associated with lethality in Colombia during 2007-2017. Methodology: Retrospective observational study that included: a descriptive cross-sectional study and an ecological design that analyzed aggregate measures of morbidity, mortality and risk attributable to the population in rural and urban areas. In the cross-sectional study, the relative risk was estimated to measure the factors associated with lethality among intoxications using Poisson regression with logarithmic function. For the time series, the trends were established with simple linear regression and the seasonal decomposition was performed using the multiplicative model. Autocorrelations were tested using the Box-Ljung statistic.Results: Between 2007-2017; 89 490 cases were reported. The Morbidity due to poisoning showed a higher proportion in the rural population 36.03 cases per 100 000; this indicator was three times higher than in urban areas (12,33 cases per 100 000). The mortality rates in rural and urban areas were 1,00 and 0,13 cases per 100 000, respectively. The relative risk of fatality in case of intoxication was associated with the intention of suicide in the rural population RR: 5.9 (95% CI: 5.0-6.9).Conclusion: A higher proportion of lethality associated with these events occurred in populations living in rural areas and reporting cases of suicidal intent. In addition, morbidity and mortality due to pesticide poisoning had the highest proportion in rural areas and a growing trend over time.